Simplifying Attribute-Based Access Control (ABAC) for Modern Enterprises - Dinesh Rajasekharan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article provides a comprehensive exploration of Attribute-Based Access Control (ABAC) and its growing importance in modern enterprise security. It begins by explaining the core principles and components of ABAC, contrasting it with traditional Role-Based Access Control (RBAC) to highlight its advantages in flexibility, granularity, and context-awareness. The article then delves into the practical aspects of implementing ABAC in organizations, discussing key steps such as assessing current systems, defining attributes, developing policies, and managing the transition. Real-world examples illustrate ABAC's application in securing cloud-native applications and managing access for dynamic workforce scenarios. The article also addresses challenges associated with ABAC implementation, including policy complexity, performance considerations, legacy system integration, and privacy concerns. Finally, it examines future trends in ABAC, such as its integration with artificial intelligence and machine learning, its role in zero-trust security models, and ongoing standardization efforts. Throughout, the article emphasizes ABAC's potential to revolutionize access management by enabling more nuanced, adaptive security policies that can better align with the complexities of modern enterprise environments.
Keywords: Attribute-Based Access Control (ABAC); Granular Access Management; Context-Aware Security Policies; Zero Trust Architecture; , Cloud-Native Security